(untitled) (Research, Society and Development, 2022)
Much is discussed about social organizations in academia and in the job market, but there is no common conceptual agreement on understanding the concepts. The objective of this article is, through bibliometric research, to obtain the definitions of social entrepreneurship, social enterprises and social business and to demystify these concepts, in addition to encouraging academics and researchers to develop research in these areas. According to the objective and purpose of this project, the research adopted a qualitative approach, the form of logical reasoning used was the inductive method and in relation to the nature of the sources used, the research is classified as bibliographic. It can be concluded that. In addition, these companies can contribute to areas that are, in principle, the responsibility of the municipal, state and federal governments, but these spheres are not able to maintain a quality service for the population, thus allowing other social organizations to replace the governments in these areas. services and serve a population in need.